E-BOOK DEVELOPMENT IN PLANETARY MOTION MATERIAL BY INTEGRATING AL-QURAN VERSES ASÂ LEARNING MEDIA FOR XI GRADE STUDENTS IN MAN 1 GRESIK - FITRI R U, RIZKI (Inovasi Pendidikan Fisika, 2017)
This Research is done based on the desire to inspire the spirit of Indonesia society to read early from students and produced the main product in the form of e-book in the planetary motion material by integrating the verses of Al-Quran. This study aimed to (1) produce e-book as learning media for XI grade students of MAN 1 Gresik in planetary motion material by integrating verses of Al-Quran that is proper to be used based on it’s validity, effectiveness and practicality, and (2) obtain the description about the properness of the e-book. This research used Research & Development (R & D) method. The data was derived from the validation assessment from three expert lecturers and one expert teacher covering material, media, language, and the Al-Quran content; learning outcomes and positive responses from 31 students of MAN 1 Gresik in class XI MIPA 1; As well as observers’ observations of the learning implementation and learning obstacles. The results showed that the e-book developed fulfill a very valid category. The acquisition of validity score was 95.45 in the material section, 92.85 in the media section, 66.67 in the language section, and 82.14 in the content of Al-Quran section. Furthermore, based on the effectiveness of the e-book in terms of students’ learning outcomes, the result was 74.19% with good category and in terms of students’ positive responses was 95.34% with very good category. Then based on the practicality of the e-book in terms of the learning process implementation, the learning process was done with very good category in the opening, main activity, and the closing section. The obstacles experienced in the learning process was the lack of laptops that can be used so that students had to use the laptop in pairs. Thus it can be concluded that the e-book in the planetary motion material by integrating the verses of Al-Quran declared eligible or proper to be used as a learning media for students in class XI MAN 1 Gresik.   Keywords: e-book, planetary motion, verses of Al-Quran, Research and Development.